(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores how literary studies can be effectively utilized to promote foreign language learning and examines various reading methods in depth. As technology continues to develop, enriching the human factor in language learning is crucial. This includes fostering learners’ critical thinking and creativity, analyzing characters’ life paths, and enhancing linguistic and grammatical competence through literature.